Phalangeal Intra-Articular Osteochondroma Caused a Rare Clinodactyly Deformity in Children: Case Series and Literature Review - Hao, Yun; Guo, Jia-Chao; Wang, Xiao-Lin; Shao, Jing-Fan; Feng, Jie-Xiong; He, Jin-Peng (Frontiers in Endocrinology, 2021)
Background: Various reasons are discovered in the development of clinodactyly. The purpose of this retrospective study was to present a group of rare clinodactyly deformity in children caused by phalangeal intra-articular osteochondroma, and evaluate the efficacy of various treatment methods. Methods: All children patients that treated for finger’s problem in our center between Jan 2017 and Dec 2020 were reviewed. A detailed analysis was made of the diagnosis and treatment methods in eight rare cases. X-rays and histopathology were applied. Results: A preliminary analysis of 405 patients in total was performed, and we included 8 cases in our final analysis. This cohort consisted of 2 girls and 6 boys, with a mean age of 5.74 ± 3.22 years (range: 2y5m to 11y). Overall, 4 patients had right hand affected and 4 patients had left hand affected. One patient were diagnosed as hereditary multiple osteochondroma (HMO) while the other 7 patients were all grouped into solitary osteochondroma. All of them proved to be osteochondroma by histopathology examination. Preoperative X-rays were used to allow identification and surgery planning in all cases. All osteochondromas were intra-articular and in the distal end of the phalanges, which is located opposite the epiphyseal growth area. All of the osteochondromas developed in half side of the phalanges. The angulation in the finger long axis was measured, resulted in a mean angulation of 34.63 ± 24.93 degree (range: 10.16-88.91 degree). All of them received surgery, resulting in good appearance and fingers turned to straight. No recurrence was recorded until now. Conclusions: This retrospective analysis indicates that 10 degree can be selected as the angulation level for diagnosis of clinodactyly deformities. What’s more important, the abnormal mass proved by X-rays should be included as the classical direct sign for diagnosis. The first choice of treatment is surgery in symptomatic osteochondromas.